ANALISIS STUDI KELAYAKAN BISNIS USAHA HISANA FRIED CHICKEN BERDASARKAN ASPEK STUDI KELAYAKAN - Dini Vientiany; Syawaliya Arifa; Tiara Tirta Dewi; Widiya wati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
his study aims to assess the business feasibility of the Hisana Fried Chicken enterprise based on key considerations in a business feasibility study. The research employs a descriptive qualitative and quantitative approach using a case study method. The analysis is conducted to obtain a comprehensive overview of the business feasibility from multiple perspectives.The results indicate that the Hisana Fried Chicken business is feasible to operate and develop. The findings reveal promising market potential, efficient operational systems, and well-structured business management. In terms of compliance, the business has fulfilled applicable licensing requirements and operates in accordance with halal and sharia principles. Furthermore, the financial performance shows positive results that support business sustainability. The existence of this business also provides positive economic and social impacts, particularly in job creation, while its environmental impact remains relatively manageable. Overall, the Hisana Fried Chicken business is considered feasible and has strong potential for further development in the culinary sector.